2002
DOI: 10.1046/j.1365-2141.2002.03842.x
|View full text |Cite
|
Sign up to set email alerts
|

The value of bone marrow examination in the staging of Hodgkin's lymphoma: a review of 955 cases seen in a regional cancer centre

Abstract: Summary. Bone marrow aspirates (BMA) and trephine biopsies (BMT) are commonly performed in the staging of patients with newly diagnosed Hodgkin's lymphoma (HL) but the value of these procedures is controversial. The purpose of this study was to evaluate the predictive value of the blood count and erythrocyte sedimentation rate (ESR) for bone marrow involvement (BMI) and the influence of BMI on stage and prognostic score. A retrospective analysis of 955 patients with newly diagnosed HL entered into clinical tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
53
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 20 publications
5
53
2
Order By: Relevance
“…Our findings correlated with those of Moid et al [7] where they reported 95% of diagnosis of Hodgkin's disease by BMB alone. Our findings is also in close agreement with that of Howell et al [12] whose study suggest that BMA does not have a significant role in detecting marrow involvement by Hodgkin's disease. Similar findings were reported by Sharma et al [13] where they diagnosed Hodgkin's disease in BMB alone.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings correlated with those of Moid et al [7] where they reported 95% of diagnosis of Hodgkin's disease by BMB alone. Our findings is also in close agreement with that of Howell et al [12] whose study suggest that BMA does not have a significant role in detecting marrow involvement by Hodgkin's disease. Similar findings were reported by Sharma et al [13] where they diagnosed Hodgkin's disease in BMB alone.…”
Section: Discussionsupporting
confidence: 93%
“…although BM involvement has been reported to be less common in Hl when compared to non-Hodgkin lymphomas (4), it is still essential to do BM staging in Hl as it has prognostic significance (5). The incidence of BM involvement in Hl in our study is consistent with the literature, which indicates a range between 3-18 % in many studies (4)(5)(6)(7)(8).…”
Section: Discussionsupporting
confidence: 92%
“…Studies have shown that the frequency of BM involvement in Hl is low and varies from 4 to 18% (4)(5)(6)(7). Hence some authors have suggested that BM studies can be done in selected high risk cases alone (5,8,9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Its incidence varies between 4% and 14% in the series reported during the past 20 years (1)(2)(3). According to the Ann Arbor staging criteria for HL, a bone marrow biopsy (BMB) is recommended for patients with any of the following: elevated serum alkaline phosphatase, stage III/IV disease, any unexplained cytopenia or radiographic/scintigraphic evidence of osseus involvement (4).…”
Section: Introductionmentioning
confidence: 99%